2021
DOI: 10.1038/s41598-021-86527-1
|View full text |Cite
|
Sign up to set email alerts
|

A short humorous intervention protects against subsequent psychological stress and attenuates cortisol levels without affecting attention

Abstract: Presentation of humor simultaneously with a stressful event has been shown to dampen the psychological and physiological responses of stress. However, whether a relatively short humorous intervention can be utilized to prevent the subsequent stress processing is still underinvestigated. Furthermore, it is unknown, whether such a humor intervention changes stress processing at a cost of cognitive functioning. According to the broaden-and-build theory inducing positive emotions may subsequently impact cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…In line with that, it was demonstrated that individuals’ ability to produce humor in distressing contexts is not compromised by depressive symptoms, negative mood states, or high perceptions of threat 51 . The result regarding unaffected subsequent performance is also consistent with previous non-clinical evidence that humor intervention during stress induction protects against psychological and physiological distress, leaving cognitive performance intact 22 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In line with that, it was demonstrated that individuals’ ability to produce humor in distressing contexts is not compromised by depressive symptoms, negative mood states, or high perceptions of threat 51 . The result regarding unaffected subsequent performance is also consistent with previous non-clinical evidence that humor intervention during stress induction protects against psychological and physiological distress, leaving cognitive performance intact 22 .…”
Section: Discussionsupporting
confidence: 88%
“…There is also experimental evidence that being exposed to humorous material attenuates negative feelings to a greater extent compared to equally positive non-humorous stimuli 21 . In addition, a research on short humorous interventions and perception of stressful events demonstrated that humor is a powerful tool to attenuate both psychological stress response and salivary cortisol levels 22 . Only one study has investigated the impact of humorous emotion regulation strategies in remitted depression; it demonstrated that the use of humor by previously depressed people to comment on a series of distressing scenes could alleviate their negative emotions, increase positive emotions, and enhance distance from adversity 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Still, since inhibition, like other forms of cognitive control, requires an immediate mental effort, it is aversive. Consequently, we prefer to rely on cognitive control processes as little as feasible 33,34 , highlighting the importance of regiments that can affect choices without resorting to inhibition 21,22,35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…(II) Food preferences are not the only factor affecting food choices. Other factors, such as impulsivity (Guerrieri et al, 2008 ; Wiers et al, 2011 ; Jones et al, 2018 ) and transitory states like hunger or stress (Nederkoorn et al, 2009 ; Froehlich et al, 2021a , b ), can strongly affect food choices. Therefore, a plausible explanation for the changes observed regarding unhealthy food items is that under the effects of the PHS, participants were more thoughtful regarding unhealthy choices, with the consequence of suppressing these choice options more frequently.…”
Section: Discussionmentioning
confidence: 99%